IICA-Canada: proposed action plan 1999-2000 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
The proposed Action Plan for the biennial 1999-2000 reflects the new realities within Canada and the desire by many Canadian groups to become more exposed and integrally linked to the americas. Given the results observed from the previous action-plans for 1996-1997 and 1998, the future of IICA in Canada as well as the Americas, provides ample opportunity for innovative partnerships in agri-food and agribusiness development.